Distinguishing difference through determining the mechanistic properties of mindfulness based art therapy - Andrea Cheshure; Gregg D. Stanwood; Theresa Van Lith; Scott M. Pickett (Current Research in Behavioral Sciences, 2023)
Objective: A randomized controlled trial was conducted to determine the unique role of the arts as a proactive mental health strategy for college students in Generation Z. Using a web-based approach, mindfulness-based art therapy, mindfulness only, and arts only are compared to a non-intervention control group to determine if arts-related interventions activate unique and distinguishable mechanisms of change. Participants: A sample of 109 college students were enrolled. Methods: Participants were randomized into a mindfulness-based art therapy, neutral clay task, mindfulness only, or a control condition for the 5-week intervention. Standardized measures of anxiety, somatic symptoms, mindfulness, stress, depression, and sleep, as well as biological saliva markers were obtained. Results: A main effect of time (pre- versus post-intervention) was found for all three interventions on perceived stress, depression and sleep, but not anxiety, somatic symptoms, or mindfulness. Analyses of difference scores across the study period demonstrated significant differences of all intervention groups from the control group in perceived stress. Additionally, the degree of change for MBAT and NCT groups significantly differed from the control group on depression. Lastly, MBAT and NCT groups had significantly different degrees of change in sleep. Conclusion: The results suggest promise for online interventions as a proactive mental health strategy for reducing stress, depression and improving sleep quality.